PROBLEM OF DEMOCRACY PROMOTION IN CONTEXT OF POSTCOLONIAL FEMINISM - V. A. Muzalevskiy (Vestnik MGIMO-Universiteta)
The article deals with the problems of democratization as a neocolonial practice. The author argues that the spread of democracy is similar in many respects to colonialism and civilizing mission as universal and even messianic phenomena. He notes that both of these phenomena, despite the similarity of their origin, have different "gender basis" (colonialism has characteristics of masculinity and civilizing mission - of femininity). The author reviewed the history of transforming the concepts of "colonialism" and "civilizing mission". Results parallels between the two phenomena are analyzed as a specific intellectual and public discourse in a particular era influenced the formation of both phenomena. Examples of national civilizing projects, their intellectual potential and influence on contemporary world politics are also considered. The echoes of colonialism and civilizing mission are visible in US and the EU doctrines of democracy promotion. Examining the evolution of approaches to democratization, the author finds the differences in strategic culture of the United States and the European Union: if the American establishment have a propensity to masculine practice of democracy promotion ("democratic enlargement", the project "Greater Middle East", etc.), and European leadership prefers feminine practices. In terms of the post-colonial feminism, this approach does not give these actors any special benefits, as it offers the ineffective governing strategy of the local population, not taking into account, and often denying the specific cultural environment of democracy promotion, paying more attention to institutional characteristics (lack of certain civil rights and freedoms, lack of transparency in the work of public authorities, etc.). The author notes that the current strategy of democracy promotion, though being more complex, creates the effect of "double discrimination", when both the local people and local women (imposing image of "a free and independent Western woman") feel that they are "colonized". Based on an analysis of the current state of democratization, the author proposes four possible scenarios for promoting democracy in the world.